2008
DOI: 10.1063/1.3027063
|View full text |Cite|
|
Sign up to set email alerts
|

Ferromagnetic spin-correlations in strained LaCoO3 thin films

Abstract: We present an element-resolved study of the valence and magnetic properties of LaCoO3 thin films grown via pulsed laser deposition. The Co L edge x-ray absorption shows that ferromagnetic (FM) order arises from a slight hole doping of the system presumably due to nonstoichiometry, which in the bulk system disrupts the low-spin state. However, even though the films are hole doped, the magnetic moments under tensile strain are much larger than the bulk system indicating that the strain can greatly increase the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
85
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 18 publications
11
85
1
1
Order By: Relevance
“…This feature of our theory is due to a reduced mixing between the Co 3d and O 2p states in the HS CoO 6 units, leading to softer HS Co-O bonds, compared to that of the LS CoO 6 units [14]. The HS/LS state has an energy gap of 0.5 eV consistent with tensile-strained FM LCO being insulating [7]. On the other hand, we show that no magnetic state is stable under compressive strain [4,6,7,12].…”
Section: Introductionmentioning
confidence: 47%
See 4 more Smart Citations
“…This feature of our theory is due to a reduced mixing between the Co 3d and O 2p states in the HS CoO 6 units, leading to softer HS Co-O bonds, compared to that of the LS CoO 6 units [14]. The HS/LS state has an energy gap of 0.5 eV consistent with tensile-strained FM LCO being insulating [7]. On the other hand, we show that no magnetic state is stable under compressive strain [4,6,7,12].…”
Section: Introductionmentioning
confidence: 47%
“…In our previous work, using local spin density approximation combined with the Hubbard U correction (LSDA+U), we have shown that a ferromagnetic state based on a homogenous intermediate spin (IS) state (S=1) can be stabilized above 3.8% tensile strain [10]. The ferromagnetic IS state is, however, inconsistent with two experimentally determined properties of strained LCO: the IS state is half-metallic while experiment shows that strained LCO is insulating [7], and a rather high critical strain of 3.8% is required, which is somewhat higher than that in experiment (~2%) [5][6][7][8][9][10]. Most recently, using a LDA+U approach, Hsu et al have shown that a HS/LS mixed state has a lower energy than that of the IS state in tensile-strained LCO on STO [28].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations